Key Factors Influencing the Increased Use of Artificial Intelligence Tools Among Students at Albukhary International University - Riadah; Amalia Hikmatul Hirosi; Mohammed Meqdam (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2026)
The rapid integration of Artificial Intelligence (AI) technologies in higher education has significantly influenced students’ learning practices, prompting increased reliance on AI-based academic tools. This study aims to analyze the key factors contributing to the growing use of AI tools among students at Albukhary International University. The research employed a qualitative, literature-based approach, using descriptive and content analysis methods to review relevant scholarly publications on AI adoption in higher education. The findings indicate that three major factors drive students’ use of AI tools: intensified academic workload and performance pressure, widespread digital accessibility and institutional technological integration, and the need for linguistic and cognitive support within an international academic environment. These factors collectively create structural conditions that encourage students to integrate AI technologies into their academic activities, particularly for writing assistance, information processing, and problem-solving tasks. The study concludes that the increasing use of AI tools among university students is not merely a technological trend but a response to academic, institutional, and learner-related demands in contemporary higher education. The findings imply that universities need to develop clear academic policies and support systems to ensure the responsible and ethical use of AI technologies while maintaining academic integrity and meaningful learning outcomes.